Examination Malpractice: The Hydra-Headed Monster and Virus in Nigerian Education System - Sa'ad, Tajudden; Dahiru, Abba Halilu (NIU Journal of Humanities, 2018)
Education is the hub and vital instrument for the achievement of full potentials and overall development of individuals in every society. According to Maduike (2011) education is the antidote to poverty and ignorance and the key for unlocking natural resources. Maduike (2011) also maintained that no nation striving for accelerated development does so without huge investment in education. Effort is being made by the government to ensure that individuals in the society are equipped with necessary knowledge, ability and skills to maximize their full potentials as human beings in order to contribute optimally to other sectors of national development. To achieve this, the individuals need to be well equipped in basic skills as to be able to contribute to the national development. To this end, education is supposed to serve the need of man and take cognizance of the survival of the individuals in the society. Thus, if examination is fraught with malpractice; this all important feedbacks mechanism becomes defeated and the educational system becomes distorted (Nwanekezi and Kalu, 2012).